Agricultural R&D spending at a critical crossroads - Pardey, Philip G.; Alston, Julian M.; Beintema, Nienke M. (2006)
Since 1980 many countries have changed the ways they invest in and organise public agricultural research and development (R&D). Support for public R&D has diminished, especially for near-market, applied, productivity-enhancing research, with funds being diverted to new agendas with environmental and food quality and safety objectives. These changes have important implications for sustaining productivity in developing countries, which in the past have relied on agricultural R&D spillovers from other countries. Some developing countries are becoming more self-reliant and developing their own R&D programs. However, the more disadvantaged countries will struggle to maintain productivity growth in the face of declining applicable spillovers.